A comprehensive evaluation of the ecological status of Wadi Mariout ponds, Egypt - Alaa I. Khedr; Mohamed H. Abdo; Radwan G. Abd Ellah; Shaimaa M. Ibrahim; Eman I. Abdel-Aal; Howayda H. Abd El-Hady; Nehad Khalifa; Heba E. A. Elsebaie; Amal A. Othman; Salem G. Salem; Mohamed E. Goher (Scientific Reports)
Abstract The present study is the first pioneer study on the ecological status of the Wadi Mariout ponds in the southern part of the Mediterranean Sea, Egypt. The physicochemical variables referred to brackish water (salinity: 12.28–16‰). The WQI indicated a lower water quality status in the western basin than the eastern one. The average TSI values (64.61 and 63.52) refer to high ecological productivity and poor water quality. However, the Arithmetic Water Quality Index (Ar-WQI) indicates the excellent water quality of the eastern pond for aquatic life, while the water quality of the western pond varies from good to very poor. The predominant groups’ species and low biodiversity indices of phytoplankton (1.29–2.2), zooplankton (1.23–1.93), and macroinvertebrates (0.45–1.85), as well as the biochemical composition of phytoplankton, reveal a high protein-carbohydrate ratio (> 11), indicating eutrophication conditions. Also, the biotic measurements show that the phytoplankton (70.7 × 106 Ind.l−1) and zooplankton (23.23 × 105 Ind.m−3) communities were more diverse and flourished in the western basin. Nevertheless, the macrobenthic invertebrates varied more in the eastern basin, 31,284 org.m−2, in compared to 5750 org.m−2 in the western one. The phytoplankton community was dominated by Chlorophyta and Cyanobacteria (79.5–93%), zooplankton by Rotifera (62.5–86.3%), and macrobenthos by Mollusca (62%) at the western basin and Annelida (38%) at the eastern one. The total bacteria count and fecal coliform value were rare in Wadi Mariout water. On the other hand, the sediment samples have more total coliform (15–3348 cfug−1) than the water (0–12 MPN/100). Wadi Mariout ponds, similar to Egyptian Delta lakes, suffer from the eutrophication phenomenon, which must be treated by controlling the feeding wastewater supplies of the ponds. The study sheds light on the current environmental status of Wadi Mariout lakes, serving as the first comprehensive study to assess water quality, record and classify biodiversity, and provide a precise assessment of the water body’s situation. This will facilitate the effective management of these important Egyptian lakes in the future.